HİCRİ I. YÜZYILDA SURİYE - TOPAL, ABDÜLKADİR (Fırat Üniveristesi, 2002)
YüksekLisans Tezi Hicri I. yy' da Suriye Fırat Üniversitesi Sosyal Bilimler Enstitüsü Tarih Anabilim Dalı 2002, s. VI + 310 Suriye'nin tarihi MÖ. 4000'lere kadar uzanır. Suriye, konumu itibariyle stratejik bir bölgede yer alır. Hicri I. yy Suriyesini konu alan bu araştırma, "Giriş" ve beş ana bölümden oluşmaktadır. "Giriş" bölümünde eskiçağlardan İslam fetihlerine kadarki zaman diliminde siyasi durumu ele alınmıştır. I. Bölümde müslümanlar tarafından fethi ve diğer siyasi olaylar, II. Bölümde Suriye'nin fiziki ve demografik yapısı, III. Bölümde idari yapısı, IV. Bölümde iktisadi yapısı, V. Bölümde de sosyo-kültürel yapısı ele alınmıştır. Anahtar kelimeler: Suriye, Filistin, Ürdün, Emeviler.

II ABSTRACT The Post Graduate Study Syria Syria in The First Century Of The Hegira The University Of Fırat The enstitute Of Social-Sciences Department Of History 2002 Pages. VI + 310 The History of Syria dates back until the year 4000 B.C. Because of its strategic structure Syria is important. This thesis which is based on Syria consists of an introduction, and five main parts. İn the introduction sectionthe structure of Syria has been that until is conquer by Muslims. In the first chapter Syria's conquer in the first the Hegira and the othe policy incidents; in the 2nd chapter the physicial and demographic structure, in the 3rd chapter its administration structure, in the 4th chapter its economical structure, and in the 5th chapter its socia-cultural structure has been studied. Key words: Syria, Palestine, Jordan, Benu Umayya
Syria in the first century of the hegira
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Tarih; History